The Education on Household Waste Bank Management into an Economic Product for Bataknese Mission Church Women - Nainggolan, Elisabeth; Desma Erica Maryati M; Hommy Dorty Ellyany Sinaga; Joni (Outline Journal of Community Development, 2024)
An environmentally friendly lifestyle is currently difficult to implement, meanwhile the use of single use product is increasing among the public, which has resulted in an increase in waste ini the living environment especially household waste. This condition has caused the current waste problem to become a global problem. Waste banks provide a solution to overcome the increasing amount of waste which can damage the environment and what’more, if waste banks are run with good management, they have the potential to generate profits that will increase economic value and empower the community. However, the term waste bank is still not very popular among the public, especially among mothers who are members of the Bataknese Mission Church, so it is important to conduct socialization about waste bank to educate mothers can broaden their knowlegde about waste banks and have an understanding of how to manage waste into economic products which can later increase household income.